(untitled) (Research, Society and Development, 2021)
Currently, an increase in the use of information and communication technologies can be observed, as well as the use of the internet. The growing demand for Distance Learning courses also converges at this point. In this scenario, there is a demand for Learning Management Systems (LMS) that provide users, among other features, alternatives for creating and managing knowledge assessments. Considering that, this article describes an LMS, developed with the objective of allowing the creation of tests composed of objective and discursive questions, with automatic correction and immediate feedback to students, using Text Mining techniques. In addition, a case study was applied to measure the results of the corrections of evaluations obtained through this tool, indicating its feasibility and the reports of teachers and students who used the tool, as well the correction performed by the tool compared to assessments carried out by teachers.